Estudio de prefactibilidad para la implementación de un servicio de monitoreo ambulatorio para la detección precoz de arritmias y eventos coronarios agudos en tiempo real - Wisky Pérez, Jorge Luis (2018)
The present project consists on the pre-feasibility study to implement a remote monitoring service for the early detection of arrhythmias and acute coronary events in real time, in Metropolitan Lima, covering 7th zone of the same. The income obtained from the aforementioned service, will be directed to private health centers that have the Cardiology area. The calculations of this demand made in the research, based on statistics, will be 108 services for the first year and 120 services for the fifth year. Given the demand, it is estimated that the investment needed to carry out the project is S/ 104 855, which includes infrastructure, equipment and materials (medical and systems); as well as the investment of working capital. To obtain investment support, a loan equivalent to 40% of the total amount will be requested. As a result of the economic and financial analysis, this project is feasible, because an economic VAN of S/ 64 725 and an economic TIR of 41,23%. Also, a financial VAN of S/ 95 599 and a financial TIR of 74%. In addition, indicators of liquidity, solvency, profitability and social impact favorable to the project were executed. Finally, the analysis and results obtained from the project are technically, economically, financially and socially feasible, therefore, the veracity of the project proposal is fulfilled.